Fault lines in education: dualization and diversification of pathways over 40 years of debate on education policy in Portugal - Alvares, M. (Sociologia, Problemas e Práticas, 2018)
The creation of Vocational Education Courses in 2012 rekindled recurring debates that shaped the process of institutionalization of basic education in Portugal and brought to light tensions between the need to diversify education pathways and to ensure equity. A diachronic analysis of educational policies was conducted based on legislation, parliamentary speeches and newspaper articles. The analysis traced the process of dualization of education in Portugal and identified six different periods that help to better understand the reasons for the recent change. It also revealed a story where actors, narratives and solutions reappear, even in face of new realities, raising theoretical questions about what drives change in policy.